1988
DOI: 10.1016/0266-7681(88)90082-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of wrist position on the minimum force required for active movement of the interphalangeal joints

Abstract: Active and passive muscle tension is discussed in relation to finger flexor and extensor tendons. Minimising active tension required to produce finger movement is seen as an important part of post-operative finger mobilisation following flexor tendon repair in which active movement is used. It is argued that "minimal active tension" in the flexors is equal to, or just exceeds, the passive tension in the extensors. A method of measuring passive tension in finger tendons has been described. In 24 volunteers, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 6 publications
0
41
0
2
Order By: Relevance
“…Edema is managed through positioning and later through compression. The transplanted hand(s) are positioned to avoid vascular compromise and edema, protect the repairs, and ensure optimum length-tension relationships between extensor and flexor tendons [26]. A dynamic crane extension outrigger orthosis (Fig.…”
Section: Initial Phase (Days 0 To 14)mentioning
confidence: 99%
“…Edema is managed through positioning and later through compression. The transplanted hand(s) are positioned to avoid vascular compromise and edema, protect the repairs, and ensure optimum length-tension relationships between extensor and flexor tendons [26]. A dynamic crane extension outrigger orthosis (Fig.…”
Section: Initial Phase (Days 0 To 14)mentioning
confidence: 99%
“…Wrist and arm position have been shown to influence peak grip forces (Hazelton et al, 1975;Berme et al, 1977;Pryce, 1980;Mathiowetz et al, 1985;Amis, 1987;Savage, 1988;Chao et al, 1989;Balogun et al, 1991;Lee and Rim, 1991;O'Driscoll et al, 1992;Su et al, 1994;Lamoreaux and Hoffer, 1995;Halpern and Fernandez, 1996;Kang et al, 1996;Richards, 1997;Werremeyer and Cole, 1997;De Smet et al, 1998;LaStayo and Hartzel, 1999;Lee and Zhang, 2004). These references and others (Cochran and Riley, 1986;Cochran et al, 2007) address the influence of aspects of the shape and size of the grasped object on grasping force.…”
Section: Past Handrail Researchmentioning
confidence: 88%
“…With a passive rehabilitation protocol, the external finger resistance is overcome by the passive manipulation, but the force applied to the tendon is very small as compared to the force applied to the tendon with active motion [21,22,31]. Schuind et al reported that the flexor tendon force during active motion of normal tendons in humans ranged from 0.98 to 28.4 N, averaging 18.6 N. However, during passive motion, the force was an order of magnitude less, ranging from 0.098 to 2.9 N, averaging 0.49 N [35].…”
Section: Discussionmentioning
confidence: 99%